2021
DOI: 10.1002/adma.202008261
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Local Cytosolic Calcium Release by Photothermal Heating for Studying Intra‐ and Intercellular Calcium Waves

Abstract: A methodology is described that allows for localized Ca2+ release by photoexcitation. For this, cells are loaded with polymer capsules with integrated plasmonic nanoparticles, which reside in endo‐lysosomes. The micrometer‐sized capsules can be individually excited by near‐infrared light from a light pointer, causing photothermal heating, upon which there is a rise in the free cytosolic Ca2+ concentration ([Ca2+]i). The [Ca2+]i can be analyzed with a Ca2+ indicator fluorophore. In this way, it is possible to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…In cancer cells, the molecular mechanisms of intercellular Ca 2+ wave (CW) propagation are mainly (1) gap-junction-based, involving internal transportation of Ca 2+ /inositol trisphosphate (IP 3 ) 163–165 and (2) paracrine-based, involving extracellular diffusion of ATP 166–168 (Fig. 3F).…”
Section: Calcium (Ca2+) Signals In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer cells, the molecular mechanisms of intercellular Ca 2+ wave (CW) propagation are mainly (1) gap-junction-based, involving internal transportation of Ca 2+ /inositol trisphosphate (IP 3 ) 163–165 and (2) paracrine-based, involving extracellular diffusion of ATP 166–168 (Fig. 3F).…”
Section: Calcium (Ca2+) Signals In Cancermentioning
confidence: 99%
“…153 In MCF-7 human breast cancer cells, photoexcitation-induced cytosolic Ca 2+ release triggers propagation of CWs in 2D-cultured contacted and non-contacted cells, as well as in 3D-cultured contacted cells. 163 The CW propagation in 2D-contacted cells requires the functional gap junctions. In HeLa cells, the transfer of IP 3 through connexin 43 (Cx43)-based gap junctions is required for intercellular communication of Ca 2+ signals via tunneling membrane nanotubes, in the absence of paracrine transmission.…”
Section: Calcium (Ca2+) Signals In Cancermentioning
confidence: 99%
“…Gold nanospheres illuminated by 532-nm laser light were shown to heat human embryonic fibroblast WS1 cells locally (Kucsko et al 2013). Owing to the low absorption of near-infrared (NIR) light (~ 650-900 nm) by biological samples (Weissleder 2001), NIR-absorbable gold nanoshells (Loo et al 2005;Gobin et al 2007;Marino et al 2017), gold nanonods (Huang et al 2006;Eom et al 2014;Yoo et al 2014;Yong et al 2014), and star-shaped gold nanoparticles (Zhu et al 2021) have been developed for photothermal stimulation in deep tissues. NIR light was also used to heat carbon nanomaterials such as carbon nanotubes (Kam et al 2005;Miyako et al 2012b) and carbon nanohorns (Miyako et al 2012a).…”
Section: Microscopic Temperature Manipulationmentioning
confidence: 99%
“…Cells cultured on or within the soft biomaterials form unique multicellular 3D structures such as spheroids and organoids (Hofer and Lutolf 2021). Recently, Zhu et al used star-shaped gold nanoparticles in MCF-7 tumor spheroid for heating and observed [Ca 2+ ] i increases in the targeted cells, followed by the propagation of Ca 2+ waves to adjacent cells (Zhu et al 2021).…”
Section: Perspectivesmentioning
confidence: 99%
“…Traditional tumor treatments continue to be the main methods for treating malignant tumors, although they have serious side effects and result in poor survival rates. To tackle the lack of monotherapy, combination therapy with multiple treatment approaches provides possibilities for tumor treatment. Photothermal therapy (PTT) integrated with anti-angiogenic therapy has shown substantial benefits in tumor treatment because of little damage to normal tissues, non-invasiveness, and excellent treatment ability. PTT ablates tumors through the thermal effect induced by near-infrared (NIR) laser-irradiated PTT agents. Moreover, the thermal effect from NIR laser irradiation can accelerate the movement of molecules and promote dissociation of the strong interactions between molecules to induce the release of ions and drugs from drug-loaded nanosystems. …”
Section: Introductionmentioning
confidence: 99%